THE MEANING OF SYIMBOL IN PENCAK SILAT PERFORMANCE OF LEMBAK TRIBE WEDDING EVENT - Marlin Marlina; Sapta Sari; Bayu Risdiyanto (SENGKUNI Journal (Social Science and Humanities Studies), 2020)
This study aims to describe the meaning of the symbol of the performance in Pencak Silat traditional marriage ceremonies in the people of Desa Tengah Padang, Talang Empat sub-district, Bengkulu Tengah Regency. This research is a qualitative study in which the data collected are in the form of words, pictures, and not numbers. The research was carried out in the Central Village of Padang, Talang Empat sub-district, Bengkulu Tengah Regency. Data collection is carried out through observation, interviews, and documentation. The instrument in this study is the researcher himself, that is, the researcher plans, conducts the research, and collects data, analyzes, presents data, and draws conclusions. Pencak silat was originally recognized as an embodiment of practical martial arts and performance art. In the Central Village of Padang, Talang Empat Pencak Silat Subdistrict, it was shown as an entertainment when the family wanted to hold a wedding and an official event, the community performed the traditional Pencak Silat art in the event "when the Lembak tribal wedding ceremony took place. The forms of presentation of Pencak Silat include various movements of Pencak Silat themselves over the opening movements of Pencak Silat Art, Offering Dance Movements, Swords, Flavors, Spells and Rabana. The meaning of the symbol consisting of the act of forming implies an attitude of openness that must be possessed by someone.